Pengaruh Tayangan Drama Thailand Bad Buddy: The Series di Platform YouTube terhadap Minat Belajar Bahasa Thailand pada Komunitas Raikantopeni - Khoirunnisa Fauziyyah; Zainal Abidin; Reddy Anggara (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the presence of a Thai drama series in the Boys Love genre, Bad Buddy: The Series. Where the drama series Bad Buddy: The Series has become popular since the end of 2021 and has attracted viewers in Indonesia, especially the Raikantopeni community. This study aims to determine whether there is an effect of Thai drama Bad Buddy: The Series on interest in learning Thai in the Raikantopeni community. The research method used is Quantitative with an explanatory survey quantitative approach. The theory used in this research is the Uses and Gratifications theory. The data collection technique used was by using questionnaires / surveys and also literature studies. The results of this study indicate that sub-variable X (Thai drama shows), namely 1) The intensity of watching the drama series Bad Buddy: The Series has a significant effect on interest in learning Thai in the Raikantopeni community. 2) The content of the message in the drama series Bad Buddy: The Series has a significant effect on interest in learning Thai in the Raikantopeni community. 3) The attractiveness of watching the drama series Bad Buddy: The Series also has a significant effect on interest in learning Thai in the Raikantopeni community.